Effects of aging on persistence of Escherichia coli (E. coli) and coliforms in poultry manure - Otuo-Akyampong, Boakye (2017)
A thesis submitted to the Department of Theoretical and Applied Biology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements of Master of Science degree in Environmental Science.